THE VOICE OF TRUTH ABOUT THE HOLODOMOR-GENOCIDE OF 1932 – 1933 IN UKRAINE. MATERIALS FROM “THE AMERICA” NEWSPAPER EDITION, 1932 - KORNOVENKO, Serhii; PASICHNA, Yulia (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article. The authors of the article aim at gaining new knowledge on the subject matter, content, and genre representation of the publications published in the 1932 “The America” newspaper concerning the Holodomor-Genocide of 1932–1933 in Ukraine. The scientific novelty is that the subject matter, content, and genre representation of the publications published in the 1932 America magazine concerning the Holodomor-Genocide of 1932 – 1933 in Ukraine have become the subject of special scientific focus for the first time. Conclusions. One of the historical sources of the voice of truth about the Holodomor-Genocide of 1932 – 1933 in Ukraine is the Ukrainian diaspora press in the United States – “The America” newspaper. It played a powerful role in informing the world about the Holodomor-Genocide of 1932 – 1933 in Ukraine. In the information war of that time, it also fulfilled the mission of deconstructing Soviet and pro-Soviet ideologies that denied and/or distorted and manipulated information about the Holodomor-Genocide of 1932 – 1933 in Ukraine. In 19 issues of “The America” newspaper from August 30 till December 27, 1932, 31 publications of various genres of materials about the “famine tragedy” in Ukraine were published. In the newspaper, the public could learn about the objective picture of the Holodomor-Genocide of 1932 – 1933 in Ukraine from such diverse materials as: telegrams; analytics; information; eyewitness accounts; reflections; criticism; stories; letters; “reports”; interviews; diverse materials that contain a story, “news,” and analytics in one. All of them are in Ukrainian. They present a holistic and unbiased picture of the famine reality of 1932 in Ukraine. For example, the following issues are covered: executions of starving peasants; punishment of peasants for forced theft; massive fleeing of peasants from villages; food crisis and starvation of peasants; content, implementation and consequences of the implementation of Soviet legislation; reasons for collectivization; causes and artificial nature of the famine; the essence of the Bolshevik regime and its attitude towards peasants; reasons for artificial deviant behaviour of peasants; repressions in the USSR, purging of the party ranks; import of grain by the USSR from abroad; forms of peasant resistance, etc. Key words: Holodomor-genocide of 1932 – 1933 in Ukraine, “The America” newspaper, peasant resistance, forced famine, collectivization.